Use of electronic resources by research scholars of Kurukshetra University. - Madhusudhan M (Electronic Library, 2010)
Purpose -- This paper focuses on the use of e-resources by research scholars of Kurukshetra University, Kurukshetra (India). The main aim is to determine the use of e-resources, users' skills in handling e-resources, and the purpose of their use. Further, the paper aims to highlight the problems faced by research scholars in accessing e-resources, their opinions on feature of e-resources, and their views on usefulness of e-resources compared to that of conventional sources. Design/methodology/approach -- The survey was conducted through a structured questionnaire circulated among 60 research scholars (PhD and MPhil) taken from different departments of Kurukshetra University and the response rate was 83 per cent. A stratified accidental random sample method was used for selection of respondents and interacting with them. These respondents were among those available in the university library during the survey period (18-28 December 2008). The responses received from the research scholars to 14 questions are presented in the form of tables and figures and analyzed by using a simple method of calculation. Findings -- The paper concludes that electronic resources have become an integral part of the information needs of research scholars at Kurukshetra University. Further, it finds that e-resources can be good substitutes for conventional resources, if the access is fast, and more computer terminals are installed to provide fast access to e-resources. Google is the most widely used search engine for locating information electronically. Practical implications -- The paper restricts the study exclusively to use of e-resources by the research scholars of Kurukshetra University. Originality/value -- Few attempts have been made to study the use of e-resources by research scholars and their impact in India. The paper highlights the use of e-resources in research at Kurukshetra University with some constructive suggestions for improvement of electronic resources and services.